The Use of Intravenous Neostigmine in Palliation of Severe Ileus - Pashtoon Murtaza Kasi (Case Reports in Gastrointestinal Medicine)
Neostigmine is a parasympathomimetic drug that acts as a reversible acetylcholinesterase inhibitor. Clinically it is used in patients with acute colonic pseudo-obstruction (ACPO or Ogilvie’s syndrome, which is a gastrointestinal motility disorder characterized by marked dilatation of the colon in the absence of mechanical obstruction), postoperative ileus, urinary retention, myasthenia gravis, and in anesthesia to reverse the effects of nondepolarizing muscle relaxants. Both bolus and infusion are noted to be effective and lead to prompt evacuation of flatus or stool with a reduction in abdominal distention on physical examination. Median duration is noted to be 4–30 minutes in some trials. Here we present our experience of using 2 mg of intravenous neostigmine to help relieve the severe abdominal distention and ileus in a patient with severe fecal impaction when all conservative measures had been futile. The most frequent side effect of the drug is abdominal pain/cramping, which was noted in our patient as well. Other complications include bradycardia which is very infrequently symptomatic to require atropine. Overall, the drug is a simple, safe, and effective strategy; and as pointed out in the previous studies, the drug appears to be underused in patients who do not have a true contraindication to its use.